Some aspects of the development of capitalism from below in Lebowa - Sender, John (My University, 1992)
The field research upon which this paper is based involved over 100 interviews, most of which were completed by Andrew Feinstein over a period of a couple of months in mid-1991. The Development Bank of South Africa may, or may not, decide to make available the full results of this work as a joint publication, for which my co-author will receive most of the credit. However, the blame for the content of this seminar paper is my own; it is designed to provoke academic discussion of the currently fashionable policies of small business promotion and the views expressed cannot be attributed to anyone but me. The issues raised in this paper are not new and it may be useful to refer very briefly to earlier research, which has provided a framework for the arguments presented here. In his work on the development of capitalism in Europe, Dobb (1963) recognised the critical role of state intervention in, as he put it, "aiding the emergence of the bourgeoisie". He referred to this support as the development of capitalism from above. A similar stress on the role of state intervention in 'short-cutting' the process of forming a national bourgeoisie in late-industrialising economies is an important aspect of Gerschenkron's (1962) analysis. More recently, Amsden (1989) and Sender and Smith (1986) have provided an account of the economic logic underlying this nurturing role of the state in a range of East Asian and African economies in the period since 1960. Finally, this paper's interpretation of the data from Lebowa has clearly been influenced by the results of my own earlier research in rural Tanzania in the 1970s and 1980s, where privileged access to state (or parastatal or CCM/TANU) resources was a crucial element in the accumulation strategies of rural capitalists (Sender and Smith, 1990). One issue to be explored in this seminar paper is the paradoxical inefficiency, or the relative lack of success, with which branches of the South African state (the Homeland Development Corporations, the Development Bank of South Africa) have intervened to support black capitalists in rural South Africa.
African Studies Seminar series. Paper presented 28 September 1992
Keywords: Capitalism. South Africa. Lebowa. Congresses; Economic development projects. South Africa. Lebowa. Finance. Congresses